The Impact of Peer Mentoring on Persistence and Retention at a Technical College - Andrews, Wade Mark (My University, 2016)
Student retention has been an ongoing challenge for colleges and universities for decades (Morrow & Akermann, 2011). Researchers have created several models that identify retention and persistence issues in 4-year colleges (Berger & Milem, 1997; Spady, 1979; Tinto, 1975; Voorhees, 1987), but models targeting the unique persistence and retention issues at technical colleges are limited. Technical college students are generally considered non-traditional (over 25 years of age) and many are also first- generation college students (Bean & Metzner, 1985). Most of these students have been out of high school for several years before they enroll at the technical college (Fike & Fike, 2008). Given the gaps in the educational journey for many technical college students, there is a need for technical colleges to provide programs that will assist these students in persisting and graduating. A peer mentoring program was implemented at one technical college to provide students with resources to increase their persistence and graduation. This qualitative study was designed to identify and understand the characteristics of a peer mentoring program that contribute to persistence and retention among participating students in a technical college environment. Semi-structured interviews were conducted with participants who were mentors, persistent mentees, and non-persistent mentees at one technical college. The results of this study suggest that peer mentoring programs can be effective in supporting the retention and persistence efforts of technical colleges.
Keywords: Dissertations; Education, Higher